Transformasi Program TJSL Bidang Lingkungan Perumda Balikpapan Menghadapi Krisis Air Baku: Penelitian - Utomo, Fransisca Yunita; Ganiem, Leila Mona (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study analyzes the Social and Environmental Responsibility (TJSL) program of the environmental sector of Perumda Tirta Manuntung Balikpapan (PTMB) as a strategy to respond to the raw water crisis that has impacted clean water services in Balikpapan City. The crisis was triggered by a decrease in the Manggar Reservoir's discharge due to sedimentation, watershed degradation, changes in land cover, and a decline in water quality. The study used a qualitative approach with a constructivist paradigm with a case study method through interviews, observations, and analysis of PTMB's internal documents and regional environmental policies. The results show that since 2025, PTMB's TJSL has begun to transform from a charitable approach to a more structured and sustainable one, focusing on raw water conservation through problem identification, stakeholder mapping, and goal formulation. Initial implementation includes mangrove planting in Batu Butok with the Enable Project, water conservation education, and community involvement, although still facing obstacles in inter-unit coordination, limited human resources, and the absence of evaluation standards. This research offers a policy framework that positions TJSL as part of corporate risk management and can serve as a reference for BUMDs and other public service agencies in aligning TJSL with operational risks, strengthening cross-sector collaboration, and implementing impact-based evaluations on an ongoing basis.